The Influence of Social Factors on Life Satisfaction in Old Age (Journal of Universal Excellence, 2026)
Research question (RQ): What is the connection between social factors and life satisfaction in old age? Purpose: The purpose of this research was to establish the influence of social factors on life satisfaction in old age. Method: The quantitative research method was used, a causal non-experimental method. As sampling data technique we used the technique of a survey questionnaire in ten statistical regions. For the analysis of causal effects and conditional associations we used the advanced statistical propensity score methods (Rubin, 2006). From the statistical set a simple random sample was chosen, we decided on proportionate stratification. For measuring life satisfaction we used Satisfaction with Life Scale (Diener), to which we added questions in order to study social factors. The research included 656 older adults aged 65 years and above, living in the home environment or in social care institutions. Results: Closely connected to life satisfaction in old age is the living conditions index (housing conditions, environment, financial situation, safety), whereas the lifestyle index (physical activity, nutrition, smoking, alcohol consumption) is less closely connected.Discussion: Life satisfaction in old age is importantly influenced by social factors – suitable living conditions and less influenced by a healthy lifestyle, both of which allow for a quality life also in old age.Society: The research has an important influence on the society, as too little attention is being devoted to the phenomenon of ageing. By alerting the public we wish to contribute towards the detabuisation of ageing and ageism. For the stable healthcare system it is important that older adults remain healthy, independent and satisfied.  Originality: The originality of the research is in the studying of social factor in the holistic model of satisfaction with life in the old age, which also includes physical, psychological and spiritual factors. Limitations/further research: The conducted research has its limitations in the chosen methodology and sample size. The results are the result of analysis, which was made on well-balanced study plan, therefore the results can be generalized to the population of older adults (65 years and above). In the future it will be necessary to pay attention to the study of elements of respective social factors indexes, and their influence on life satisfaction.
Keywords: social factors; living conditions; lifestyle; old people; home environment; social care institution